Understanding the Learning Disabilities Linked to Sagittal Craniosynostosis. Issue 2 (March 2019) - Cabrejo, Raysa; Lacadie, Cheryl; Brooks, Eric; Beckett, Joel; Sun, Alexander; Yang, Jenny; Chuang, Carolyn; Eilbott, Jeffrey; Duncan, Charles; Steinbacher, Derek; Alperovich, Michael; Ventola, Pamela; et al.
Abstract : Objective: The purpose of this study is to investigate further findings that corroborate similarities between corrected sagittal craniosynostosis and attention deficit hyperactivity disorder (ADHD). The aim is to further characterize the neurocognitive deficits seen in adolescents with corrected craniosynostosis by comparing it to established learning deficits such as ADHD. Methods: A total of 30 functional magnetic resonance imaging (fMRI) of 10 sagittal nonsyndromic craniosynostosis (sNSC), 10 ADHD-combined, and 10 control adolescents were studied. The fMRI scans were analyzed utilizing Statistical Parametric Mapping (University College London, UK) and analyzed with BioImageSuite (Yale University, New Haven, CT). Results: The ADHD has lower connectivity to Brodmann area (BA) 11 (Montreal Neurological Institution [MNI]: −12, 26, −21), BA20 (MNI: 62, −24, −25), and BA21 (MNI: 62, −32, −23) compared to sNSC and controls ( P < 0.001). The sNSC has a unique visuospatial defect, compared to ADHD, created by decreased connectivity to BA31 (MNI: −3, −68, 37), BA7 (MNI: −4, −68, 41), BA19 (MNI: 0, −83, 31), visual association cortex (MNI: −4, −78, 22), and primary visual cortex (MNI: 7, −74, 21) ( P < 0.001). Conclusion: Patients born with sNSC have different neural connections than children born with ADHD. Patients born with sNSC have decreased connections in areas of visual processing and increased connections in areas of attention and auditory processing than patients with ADHD. Therefore, children with sagittal craniosynsotosis may have learning difficulties that, similar, yet different from ADHD.